Regulation of intracellular free calcium concentration during heterocyst differentiation by HetR and NtcA in Anabaena sp. PCC 7120 - Shi, Yunming (National Academy of Sciences, 2006)
Calcium ions are important to some prokaryotic cellular processes, such as heterocyst differentiation of cyanobacteria. Intracellular free Ca(2+)concentration, [Ca(2+)](i), increases several fold in heterocysts and is regulated by CcbP, a Ca(2+)-binding protein found in heterocyst-forming cyanobacteria. We demonstrate here that CcbP is degraded by HetR, a serine-type protease that controls heterocyst differentiation. The degradation depends on Ca(2+) and appears to be specific because HetR did not digest other tested proteins. CcbP was found to bind two Ca(2+) per molecule with K(D) values of 200 nM and 12.8 μM. Degradation of CcbP releases bound Ca(2+) that contributes significantly to the increase of [Ca(2+)](i) during the process of heterocyst differentiation in Anabaena sp. strain PCC 7120. We suggest that degradation of CcbP is a mechanism of positive autoregulation of HetR. The down-regulation of ccbP in differentiating cells and mature heterocysts, which also is critical to the regulation of [Ca(2+)](i), depends on NtcA. Coexpression of ntcA and a ccbP promoter-controlled gfp in Escherichia coli diminished production of GFP, and the decrease is enhanced by α-ketoglutarate. It was also found that NtcA could bind a fragment of the ccbP promoter containing an NtcA-binding sequence in a α-ketoglutarate-dependent fashion. Therefore, [Ca(2+)](i) is regulated by a collaboration of HetR and NtcA in heterocyst differentiation in Anabaena sp. strain PCC 7120.